Penerapan Instrumen Three-Tier Test untuk Mengidentifikasi Miskonsepsi Siswa SMA pada Materi Keseimbangan Benda Tagar - Astuti, Budi; Fitrianingrum, Aufa Maulida; Sarwi, Sarwi (Sains and Technology Faculty, Walisongo State Islamic University, 2017)
The purpose of this research was to identify and analyze the studentsâmisconceptions ofrigid body equilibrium concept. This research was included inertia moment, torque, andcentre of gravity concept. This reseacrh used qualitative method. There were 35 students assample chosen by purposive sampling technique. The research data was obtained bydiagnostic test used three-tier test. Based on the qualitative analysis result to the studentsâanswers could be conclude that there were misconceptions. The high misconceptions werehappenned in moment inertia concept and cognitive domain ârememberâ.